Effect of modified clivoaxial angle on surgical decision making and treatment outcomes in patients with Chiari malformation type 1 - Akyuz, Mehmet Emin; Karadag, Mehmet Kürşat; Sahin, Mehmet Hakan (Frontiers in Surgery, 2023)
Introduction: Chiari malformation type 1 (CM1), a complex pathological developmental disorder of the craniovertebral junction, is typically characterized by herniation of the cerebellar tonsils from the foramen magnum. Treatment using posterior fossa decompression alone without taking the ventral cervico-medullary compression into consideration may lead to unsatisfactory treatment outcomes. The current study evaluated the utility of the modified clivoaxial angle (MCAA) in assessing ventral compression and also examined its effect on treatment outcomes. Method: This retrospective study included 215 adult patients who underwent surgical treatment for CM1 at one medical center over a 10-year period. The following surgical techniques were used to decompress the posterior fossa: a) PFD: bone removal only; b) PFDwD: bone removal with duraplasty; and c) CTR: cerebellar tonsil resection. The morphometric measurements of the craniovertebral junction (including MCAA) were recorded using preoperative images, and the postoperative clinical status was evaluated using the Chicago Chiari Outcome scale (CCOS). Results: MCAA was positively correlated with the CCOS score and also independently predicted treatment outcome. To enable Receiver operating characteristic (ROC) curve analysis of CCOS scores, the patients were divided into three groups based on the MCAA cut-off values, as follows: a) severe (n = 43): MCAA≤ 126; b) moderate (n = 86): 126 < MCAA ≤ 138; and c) mild (n = 86): MCAA > 138. Group a exhibited severe ventral cervico-medullary compression (VCMC), and their CCOS scores for the PFD, PFDwD, and CTR groups were 11.01 ± 1.2, 11.24 ± 1.3, and 13.01 ± 1.2, respectively (p < 0.05). The CCOS scores increased with widening of the MCAA angle in all surgical groups (p < 0.05). Furthermore, patients with mild MCAA (>138°) exhibited 78% regression of syringomyelia, and this was significantly greater than that observed in the other groups. Discussion: MCAA can be used in the selection of appropriate surgical techniques and prediction of treatment outcomes, highlighting the importance of preoperative evaluation of ventral clivoaxial compression in patients with CM1.